The Influence of Organizational Culture, Work Environment, and Leadership on Employee Performance PT Talenta Heba Parnita Depok - Harini, Sri; Kartini, Tini; Muzdalifah, Gina (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2024)
This study aims to determine the direct influence of organizational culture, work environment, and leadership on employee performance at PT Talenta Heba Parnita Depok. The sample in this study 57 people were using the method of determining saturated sampling techniques. The instrument test technique in this study uses the IBM Statistical Package For Social Sciences (SPSS) software application with the regression analysis method. The results showed that organizational culture, work environment, and leadership simultaneously and partially had a positive and significant effect on employee performance.